Relating to Things Design, Technology and the Artificial - Wiltse, Heather (Bloomsbury Academic, 2020)
We relate to things and things relate to us. Emerging technologies do this in ways that are interesting and exciting, but often also inaccessible or invisible. In this open access book, leading design researchers and philosophers respond to issues raised by this situation - inquiring into what it means to live with and relate to things that can actively relate to us, and that relate to each other in ways that do not involve us at all. Case studies include Amazon's Alexa, the Internet of Things, Pokémon Go and Roomba the robot vacuum cleaner. Authors explore everything from the care work undertaken by objects, reciprocal human/machine learning, technological mediation as a form of control, and what it takes to reveal things that tend to be hidden and that often (by design) conceal the ways in which they use us. As a whole, Relating to Things is a collaborative philosophical inquiry into the nature and consequences of contemporary technological things. It is a design inquiry into the current nature of the artificial, and possibilities for how things might be otherwise. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.